An innovative modal approach for frequency domain stress recovery and fatigue damage evaluation. (October 2016) - Braccesi, Claudio; Cianetti, Filippo; Tomassini, Lorenzo
Abstract: The aim of the present paper is to show and validate an innovative method, developed by authors to evaluate, in frequency domain, the fatigue damage of mechanical components modeled by modal approach and subjected to random dynamic loads. The authors, in particular, have theoretically demonstrated that the exact statistical properties ( spectral moments ) of the PSD functions matrix of stress tensor of the model are obtainable only from PSD functions matrix of its modal coordinates and from PSD functions matrix of inputs. To show the capabilities of this new approach and to verify the obtainable speeding up of the evaluation process two test cases are analyzed and discussed.